A inteligência competitiva como difusora da ação estratégica: diagnóstico do setor vinícola de Bento Gonçalves - RS - Roman, Cirilo Mário (2001)
The transformation that occurs in the scenery of the companies at this moment, leads them to a competitive environment, making exist more demands of the organizations, turning them more efficient. The companies search each time for more knowledge to follow this transformation, existing the concerning in the adequate way of arranging an organizational strategy that really works. The companies that really get to stand out through a clear, flexible and evolutive strategy have some strength that leads them, followed by directed information to the development of this strategy. This essay analyses the competitive intelligence of the winegrowing sector of Bento Gonçalves, through the establishment of the variable motive-power, organizational strategy and distinguished information. This way, we seek to make a research of this sector improving its peculiarities. The essay starts with the definition of the problem, characterizing the sector through a historic, problem and studied theme. On the theoretical reference, there is an evolution through the variable considered vital to the instauration of the competitive intelligence, beginning from the information to motive-power, organizational strategy, to the strategic information directed to the action. The results of this essay are in a chapter (Competitive Intelligence Analysis), which has the objective to analyze the research through a diagnosis of the winegrowing sector. This essay evaluates the winegrowing sector of Bento Gonçalves, with clear and defined strategies according to its objectives, but it¿s still not achieving in its greatest part to establish an organizational competitive intelligence.